Unveiling the molecular architecture of the mitochondrial respiratory chain of Acanthamoeba castellanii - Christian Q. Scheckhuber; Sutherland K. Maciver; Alvaro de Obeso Fernandez del Valle (Microbial Cell)
Acanthamoeba castellanii is a ubiquitous free-living amoeba that can cause severe infections in humans. Unlike most other organisms, A. castellanii possesses a “complete” mitochondrial respiratory chain, meaning it contains several additional enzymes that contribute to its metabolic versatility and survival in diverse environments. This review provides a comprehensive overview of the mitochondrial respiratory chain in A. castellanii, focusing on the key alternative components involved in oxidative phosphorylation and their roles in energy metabolism, stress response, and adaptation to various conditions. The functional characterization of the alternative oxidase (AOX), uncoupling protein (UCP), and alternative NAD(P)H dehydrogenases, highlight their roles in reducing oxidative stress, modulating proton gradients, and adapting to changes in temperature and nutrient availability. These proteins and systems serve a role in the survival of A. castellanii under stressful conditions such as starvation and cold conditions. Further knowledge of the respiratory chain of the amoeba has potential implications for understanding the evolution of mitochondrial respiration and developing new therapies for treating Acanthamoeba infections.